Morrittospora corbiculae n. gen. n. sp., a microsporidian parasite infecting the invasive Asian clam Corbicula fluminea from the River Thames, London - Rachel Foster; Kelly S. Bateman; Paul F. Clark; Matthew J. Green; Chantelle Hooper; Stuart H. Ross; Paul Stebbing; Georgia M. Ward; David Bass (Journal of Invertebrate Pathology, 2026)

Revising supraglacial rock avalanche magnitudes and frequencies in Glacier Bay National Park, Alaska - William D. Smith; Stuart A. Dunning; Neil Ross; Jon Telling; Erin K. Jensen; Dan H. Shugar; Jeffrey A. Coe; Marten Geertsema (Geomorphology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Using CBPR to Extend Prostate Cancer Education, Counseling, and Screening Opportunities to Urban-Dwelling African-Americans - Levi Ross; Jarrett Johnson; Stacy W. Smallwood; John S. Luque; Stuart H. Tedders; Collins O. Airhihenbuwa; Terry Alford; Willie Underwood (Journal of Cancer Education, 2016)

Ecological and socio-economic factors affecting extinction risk in parrots - George Olah; Stuart H. M. Butchart; Andy Symes; Iliana Medina Guzmán; Ross Cunningham; Donald J. Brightsmith; Robert Heinsohn (Biodiversity and Conservation, 2016)

Possible impacts of anthropogenic and natural aerosols on Australian climate: a review - Leon D. Rotstayn; Melita D. Keywood; Bruce W. Forgan; Albert J. Gabric; Ian E. Galbally; John L. Gras; Ashok K. Luhar; Grant H. McTainsh; Ross M. Mitchell; Stuart A. Young (International Journal of Climatology, 2009)
A review is presented of the aerosol–climate interaction with specific focus on the Australian region. The uncertainties associated with this interaction are much larger than those associated with greenhouse gases or other forcing agents, and are currently a major obstacle in climate‐change research. However, new research suggests that aerosol effects are of comparable importance to greenhouse gases as a driver of recent climate trends in the Southern Hemisphere, including Australia. A significant new result from climate modelling is that anthropogenic aerosol over Asia affects meridional temperature gradients and atmospheric circulation, and may have caused an increase in rainfall over north‐western Australia. Global ocean circulation provides another mechanism whereby aerosol changes in the Northern Hemisphere can affect climate in the Southern Hemisphere, suggesting an urgent need for further targeted studies using coupled ocean‐atmosphere global climate models. To better model climate variability and climate change in the Australian region, more research is needed into the sources of aerosol and their precursors, their atmospheric distributions and transformations, and how to incorporate these processes robustly in global climate models (GCMs). The following priorities are suggested for further research in Australia linking aerosol observations and modelling: natural aerosol over the Southern Ocean, tropical biomass‐burning aerosol in Indonesia and Australia, secondary organic aerosol (SOA) from volatile organic compounds (VOCs), wind‐blown dust and modulation of rainfall by anthropogenic aerosol. Copyright © 2008 Royal Meteorological Society

Gastrointestinal Parasites in Crop Raiding and Wild Foraging Papio anubis in Nigeria - Anna H. Weyher; Caroline Ross; Stuart Semple (International Journal of Primatology, 2006)

Distribution and diversity of soil protozoa in the McMurdo Dry Valleys of Antarctica - Stuart S. Bamforth; Diana H. Wall; Ross A. Virginia (Polar Biology, 2005)